If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 5x = 2(4 + -1x) + -6 -12 + 5x = (4 * 2 + -1x * 2) + -6 -12 + 5x = (8 + -2x) + -6 Reorder the terms: -12 + 5x = 8 + -6 + -2x Combine like terms: 8 + -6 = 2 -12 + 5x = 2 + -2x Solving -12 + 5x = 2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -12 + 5x + 2x = 2 + -2x + 2x Combine like terms: 5x + 2x = 7x -12 + 7x = 2 + -2x + 2x Combine like terms: -2x + 2x = 0 -12 + 7x = 2 + 0 -12 + 7x = 2 Add '12' to each side of the equation. -12 + 12 + 7x = 2 + 12 Combine like terms: -12 + 12 = 0 0 + 7x = 2 + 12 7x = 2 + 12 Combine like terms: 2 + 12 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 200-.33x=80 | | 5(-4q-16)-7q=13+19-11q | | 6.4+1.8n=2.08 | | -12+5x=8-2x-6 | | 200-.5x=80 | | -1.3s+2.78=15.59+2.3s-2.9s | | 5(x+2)=2(x+2)+7 | | 42-8m=13m | | 34(18-4.5x)=16(4x-9)+61.6 | | -2(t+4.667)=9.5 | | -19.21+12.2g=0.9g | | 18-5y=3x-6 | | 35=5n+10 | | -11.3h-17.63=10.2h+18.92 | | 5(x+4.1)=10x-1.5 | | 8x+4(4x-3)=4(3x+4)-8 | | 13.5f+11.06+1.7f=10.34+17f | | 6x=171 | | 3a-15=-21 | | 7-(x+4)=34 | | 0.6(y-10)=0-y | | -18.9u=-18.1u+14.96 | | y-7=1.5x-6 | | y=x-17 | | 19+14j=17j-11 | | 3y-21=27 | | 6(x-1)-3=4x+2(-4+x) | | 45=300 | | 9(2r+4)=4(5r-1) | | 8(x+4)=2x+68 | | 7-g=6 | | 9.6t+6=30 |